Restauração ecológica em floresta tropical seca no Brasil - Amorim, Isaac Lucena de (2022)
Every year the expansion of degraded areas increases, especially in biomes subject to the influence of arid, semi-arid and dry subsumed climates. This problem gave rise to the Science of Restoration Ecology, based on ecological, agronomic and silvicultural knowledge for the development and application of ecological theories and models in the practices of restoration of degraded ecosystems. Based on this science, two restoration techniques were evaluated in a degraded area of the semi-arid region of Paraiba, at San Porfirio Waterfall Farm, municipality of Várzea: Natural Regeneration (RN) and Passive Nucleation (NP), with the following objectives: RN, to know the floristic composition, phytosociological structure and biomass of the regenerating herbaceous-subshrub community, whose data will be important to monitor succession over time; NP, to verify the nucleating potential of antlers and perches as attractants for seed dispersers and plant establishment. For the study of the RN herbaceous-subshrub community, 20 plots of 2.0 m × 2.0 m were demarcated, and each plot was subdivided into four subplots of 1.0 m2 (one for biomass collection in the rainy season, another for of biomass in the dry season, the third to carry out the floristic/phytosociological survey and the fourth subplot for soil collection, aiming at chemical analysis). This study was developed in the year 2020. For the study of passive nucleation, 04 treatments were evaluated (different distances between nuclei), in randomized blocks, with 04 repetitions, with the antlers measuring 0.7 m3 and the perches with about 2.0 m in height, consisting of branches fixed to a wooden column and at the base a 1.0 m2 shade screen for monthly collection of bird excreta. This study took place over two years (August 2019 to July 2021). As a result, in the area in RN, 35 species of herbaceous/subshrub plants were identified, of which 23% belong to the Fabaceae family. Although the only representative of the Poaceae family, panasco grass (Aristida adscensionis) was the most abundant and with the highest Importance Value. The plant community presented a diversity index (H') of 1.82 (nats ind-1) and a species richness of the order of 3.61 (In ind)-1 individuals in relation to the number of species. It was found that the biomass produced in the wet season was reduced by more than 90% in the dry season. In the treatments with NP, it was observed that the antlers provided shelter for the fauna and also favored the accumulation of organic matter in the soil; the artificial perches were important attractions for bird dispersers, with the most distant ones being the most visited by the 22 species of birds identified. Therefore, for the northeastern semi-arid conditions, the ecological restoration techniques tested proved to be promising, although their successes are directly dependent on the characteristics of the rainy season.